Tuberculosis in Vaccinated versus Unvaccinated Children with BCG Vaccine in Niamey: Epidemiological, Diagnostic and Outcome Aspects - Aboubacar, Samaila; Alido, Soumana; Moumouni, Kamaye; Djafar, Mamoudou Abdou; Moumouni, Garba; Madougou Assiatou, Gagara Issoufou; Abasse, Moussa Ounteini; Boubacar, Marou Soumana; Habiba, Ide Amadou; Nafissatou, Nanaito; Ibrahim, Georges Thomas (European Scientific Journal, ESJ, 2022)
Introduction: Tuberculosis remains a public health problem worldwide. The BCG vaccination is one of response means. The objective of this work was to study impact of BCG vaccination on morbidity and mortality related to childhood tuberculosis in Niamey. Patients and methods: It was a multicenter prospective and comparative study from January to September 2017 in two-referral hospital centers of Niamey and the National Anti-Tuberculosis Center. The study population consisted exhaustively of children aged 0 to 15 years old suffering from tuberculosis. Epidemiological, diagnostic and evolving aspects in vaccinated and unvaccinated children were studied. Statistical tests used were Pearson’s Chi² and Fisher’s exact test (p <0.05). Results: Ninety-one children were studied. The BCG vaccination rate was 60.4%. The mean age of children was 6 years 11 months [3 months-15 years]. Children under 2 years of age were less affected (11%) in vaccinated children than in unvaccinated children (3.2%). No association was found between duration of tuberculosis signs (p = 0.37), expression of tuberculin skin test (p = 0.43), and the children’s BCG vaccination status. On the other hand, there was a significant link between vaccination status and the results of microscopic examination of sputum or gastric fluid (p = 0.02), occurrence of complications (p = 0.014) and death risk (p = 0.003). Conclusion: This study shows that children’s BCG vaccination status interferes with some aspects of tuberculosis. Therefore, fighting against tuberculosis must be intensified, through combination of many strategies including vaccination.